THE EFFECT OF IMPLEMENTATION PHOTOGRAPHY LEARNING MEDIA BASED ON LEARNING INQUIRY FOWARD STUDENT LEARNING RESULT AT XI-MM SMK 1 MAS IN THE ACADEMIC YEAR 2012/2013 - Dewa Gede Agus Dharmadi (Universitas Pendidikan Ganesha, 2013)
The purpose of this research was (1) to find out the effect of implementation photography learning media based on learning inquiry foward student learning result at xi-mm smk 1 mas in the academic year 2012/2013, (2) To find out the response of students of class XI-TMM SMK N 1 Mas towards the implementation of inquiry-based learning media photography in the process of learning photography.The type of this research was a quasi-experimental research with a research design that used nonequivalent pretest-posttest control design. Population of this research was a class XI student of SMK Negeri 1 Mas MM academic year 2012/2013 with a sample using MM2 as a student of class XI and XI MM2 experimental group as the control group with the total number of students by 78 students. At the beginning of learning first given a pre-test on a sample of second-class multiple-choice test and a final study sample of both classes were given a multiple choice test (Cognitive) using the same instrument. The test has been analyzed using qualitative analysis and quantitative analysis. Data collection was performed by the method of multiple-choice test to measure cognitive domains. The method tests were conducted to obtain data on the final value after being treated in the experimental group and the control group.There are a prerequisite test to be done that is, test for normality and homogeneity tests. Data were analyzed using ANOVA,Based on the results of normality and test homogeneity. Of the data of the two groups of data obtained both normal and homogeneous samples. By using the ANOVA hypothesis testing, the results of calculations obtained while the value of F = 68.326 Theoretical = 3.97, by> F Theoretical then Ho is rejected and Ha accepted. For as much as 34.21% of student responses students gave very positive responses, 63.16% of students responded positively, 2.63% of students responded quite positively.